2003
DOI: 10.1136/gut.52.5.671
|View full text |Cite
|
Sign up to set email alerts
|

An Asia-Pacific, double blind, placebo controlled, randomised study to evaluate the efficacy, safety, and tolerability of tegaserod in patients with irritable bowel syndrome

Abstract: Tegaserod 6 mg twice daily is an effective, safe, and well tolerated treatment for patients in the Asia-Pacific region suffering from IBS and whose main bowel symptom is not diarrhoea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
166
3
6

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(187 citation statements)
references
References 25 publications
12
166
3
6
Order By: Relevance
“…However, later human and animal research has produced equivocal results regarding sex differences in opioid analgesia [43]. Some evidence indicates that serotonergic agents (5HT 4 agonists, 5HT 3 antagonists) may be more efficacious in alleviating IBS symptoms in women than in men [30,97,145,151]. However, these clinical trials have been criticized because the higher frequency of IBS in females skewed the sex distribution.…”
Section: Is There Enough Evidence To Warrant Sex-specific Pain Intervmentioning
confidence: 98%
“…However, later human and animal research has produced equivocal results regarding sex differences in opioid analgesia [43]. Some evidence indicates that serotonergic agents (5HT 4 agonists, 5HT 3 antagonists) may be more efficacious in alleviating IBS symptoms in women than in men [30,97,145,151]. However, these clinical trials have been criticized because the higher frequency of IBS in females skewed the sex distribution.…”
Section: Is There Enough Evidence To Warrant Sex-specific Pain Intervmentioning
confidence: 98%
“…It stimulates intestinal secretion of water and chloride and decreases the nociceptive response to rectal distension [58] . Several large, randomized-trials have shown that tegaserod has a significant impact on a patient's overall assessment of global relief, and that it statistically improves abdominal pain and bloating [59][60][61][62] . A 2004 Cochrane metaanalysis supported these results by concluding that tegaserod was associated with improvement in global relief of GI symptoms [relative risk (RR), 1.17; 95% CI, 1.08-1.27] and that it improved bowel consistency and frequency [63] .…”
Section: -Ht4 Agonistsmentioning
confidence: 99%
“…15 Drug development tools (DDTs) intended for potential use, over time, in multiple drug development programs include, but are not limited to, biomarkers and clinical outcome assessments including PRO instruments. FDA qualification is a conclusion that within the stated context of use, the results of assessment with a DDT can be relied upon to have a specific interpretation and application in drug development and regulatory decision-making.…”
Section: Future Development Of Ibs Pro Instrumentsmentioning
confidence: 99%